Structure and Transport in Coatings from Multiscale Computed Tomography of Coatings—New Perspectives for Eelectrochemical Impedance Spectroscopy Modeling?. (1st June 2016) - Hughes, A.E.; Trinchi, A.; Chen, F.F.; Yang, YS.; Sellaiyan, S.; Carr, J.; Lee, P.D.; Thompson, G.E.; Xiao, T.Q.
Abstract: Computed Tomography (CT) is an approach that has been extensively applied in many areas of science from understanding structures in living organisms to materials science. In materials science, the study of structures within coatings presents challenges on at least two different levels. First, the structure of the coatings needs to be understood from the atomic scale, where dissolution reactions begin, up to length scales which cover the aggregation of inhibitors and other additives, which take place at ∼10 −5  m, i.e. 4 to 5 orders of magnitude. CT is a favourable imaging technique since it allows multiscale information to be obtained non-destructively down to tens of nanometres. In this study X-ray absorption contrast imaging has been used to examine structures created using strontium chromate (SrCrO4 ) particles embedded in an epoxy film. It has been found that SrCrO4 particles can form clusters that extend a few hundred microns in the plane of the film, span the thickness of the film and have fractal characteristics. There are also volumes of low density epoxy of similar sizes and characteristics to the SrCrO4 clusters. The SrCrO4 clusters have a strong influence on the leaching behaviour since the release changes with time. Initially, leaching is controlled by direct dissolution but, as the clusters dissolve, the release is dominated by the fractal dimension of the cluster. The dissolved clusters leave behind voids filled with electrolyte that provide alternative transport pathways for corrosive ions through the polymer. In this paper, the nature of these clusters will be reviewed and the implication for transport properties and electrochemical assessment will be explored.